Post colonoscopic acute bacterial prostatitis: a case report - Rashid, Rahim A.; Karthikeyan, Ramalakshmi (International Journal of Research in Medical Sciences, 2021)
Colonoscopy is a common procedure for diagnosing a wide range of conditions and symptoms affecting the large bowel. Research has shown that the examination itself may induce transient bacterial infections. Specifically acute bacterial prostatitis (ABP) has little mention in medical literature as a recognized complication of this procedure. Here we discuss a 37 year old male presenting with symptoms suggesting lower urinary tract infection after having undergone colonoscopy followed by recurrent episodic haematuria and lower urinary tract symptoms (LUTS). Physicians and endoscopists should be aware of the risk of acute bacterial prostatitis as a potential complication of colonoscopy in order to minimize misdiagnosis as well as the complications associated with the delayed treatment of it. In addition male patients and the immunocompromised should be fully counselled regarding this risk prior to undertaking this procedure.